The nature of antiglobulin reactivity of antibody to penicillin - Watson, K. C. (1964)
Haemagglutinin is present in certain sera from patients treated with benzylpenicillin and causes direct haemagglutination of benzylpenicillin coated erythrocytes. Direct agglutinating activity is present in the 19S macroglobulin component and is destroyed by 2-mercaptoethanol. Antiglobulin activity which is due to 7S antibody is not affected. Studies showed that the antiglobulin activity is usually of anti-gamma type. Thus, all of eighteen sera treated with 2-mercaptoethanol gave anti-gamma reactions and four also gave weak anti-non-gamma reactions. The latter did not appear to be due to complement adsorption and the reason for these is not immediately apparent but may be due to non-specific adsorption of other proteins. In five of twelve sera tested the titres showing positive antiglobulin reactions were higher than the direct haemagglutinin titres performed in saline. Absorption of these sera with heterologous methicillin coated cells, following treatment with 2-mercaptoethanol, still left antiglobulin sensitizing activity, presumably due to antibody reacting with side chain determinant groups of the benzylpenicillin molecule. Benzylpenicillin in solution did not completely inhibit adsorption of 7S antibody to penicillin coated cells, although reducing the titre of the serum which would give a positive antiglobulin reaction (similar concentrations of penicillin prevent completely direct agglutination in saline). However, when normal erythrocytes were used in place of benzylpenicillin coated cells, in the presence of serum dilutions and benzylpenicillin in solution, higher titres were observed than was the case with coated cells. This suggests that 7S—penicillin complexes formed in solution attached more readily to normal cells than did 7S antibody to already cell bound penicillin. Coated erythrocytes exposed to 7S antibody appeared to exert a partial blocking effect on 19S direct agglutinating activity. Reversal of haemagglutination occurs following direct agglutination in saline but the cells still contain sufficient adsorbed 7S antibody to give a positive antiglobulin test. Separation of sera on DEAE—cellulose columns with step-wise gradient elution resulted in 7S activity being found in the first elution fractions (0.01 M phosphate buffer, pH 7.0). Macroglobulin activity is located in later fractions (0.15 M phosphate buffer plus 0.15 M NaC1, pH 5.0) and treatment of this fraction with 2-mercaptoethanol failed to show sensitizing activity, indicating that the monomeric units obtained by dissociation of S—S bonds are not identified with the normal 7S component responsible for sensitizing activity.